(untitled) (Journal of Bio-Science, 2026)
Avian colibacillosis is considered as one of the principal causes of morbidity and mortality, associated with heavy economic losses to the poultry industry. The study was conducted for observation of prevalence and pathological investigation of colibacillosis in commercial poultry farm at city corporation area of Rajshahi, Bangladesh during the period from July 2023 to June 2024. Escherichia coli was isolated from 82.7% of cloacal swabs of apparently healthy birds and 85.0% of sick and dead birds. Average prevalence of colibacillosis, on the basis of age, was higher (65%) in age group 0–2 weeks and lower in >4 weeks (10%). The higher prevalence of colibacillosis was in winter (65%) and lower in summer season (35.71%). In colibacillosis, congested and consolidated lungs with cloudy and thickened air sacs, congested and thickened liver capsules, and enteritis were observed at necropsy. The microscopic lesions were hemorrhage in liver and huge infiltration of heterophils, highly congestion in lung, blunting of villus and reactive cell infiltration, and thickening of fibrous tissue in pericardium. In conclusion, a higher prevalence of colibacillosis (>80%) was observed in commercial poultry farms of city corporation area of Rajshahi, and age and season were the significant risk factors of colibacillosis in broiler chickens. J. Bio-Sci. 33(1): 41-52, 2025